2021
DOI: 10.1016/j.isci.2021.102402
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Batf3 reveals a new dimension of cell state heterogeneity within conventional dendritic cells

Abstract: Single-cell proteogenomics identifies additional layers of DC heterogeneity cDC diversity is driven by proliferation, developmental stage, and maturation Lack of Batf3 increases cDCs with lineage-mixed features Sox4+ cDCs represent a cell state of lineage-mixed features

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 51 publications
0
17
0
Order By: Relevance
“…Several scRNA-seq studies supported similar populations as cDC precursors ( 44 , 46 , 63 ). Similarly, Lukowski et al ( 64 ) identified a cluster of Sox4 + cDCs in the murine spleen, displaying a continuum of cDC and pDC lineage-mixed gene signatures, which had a similar transcriptional profile with AS DCs in humans. This population expressed elevated levels of pre-DC features (such as CX3CR1, FLT3, CD33, and CSF1R) and was hypothesized to represent a cell state of pre-DC to cDC transition.…”
Section: Applications Of Scrna-seq In DC Studiesmentioning
confidence: 89%
“…Several scRNA-seq studies supported similar populations as cDC precursors ( 44 , 46 , 63 ). Similarly, Lukowski et al ( 64 ) identified a cluster of Sox4 + cDCs in the murine spleen, displaying a continuum of cDC and pDC lineage-mixed gene signatures, which had a similar transcriptional profile with AS DCs in humans. This population expressed elevated levels of pre-DC features (such as CX3CR1, FLT3, CD33, and CSF1R) and was hypothesized to represent a cell state of pre-DC to cDC transition.…”
Section: Applications Of Scrna-seq In DC Studiesmentioning
confidence: 89%
“…These data suggest there may be two possible cross presentation pathways for IEC-derived antigen: one that occurs in the presence, and one in the absence, of inflammatory signals. Indeed, recent work shows that cDC2s can take on characteristics of cDC1s under inflammatory conditions (Bosteels et al, 2020) or in the absence of Batf3 (Lukowski et al, 2021), though it remains uncertain if these cells are able to cross prime CD8 + T cells or provide T cells with the appropriate homing signals. Perhaps IL-18 and/or other inflammatory signals downstream of NAIP–NLRC4 activation can activate cDC1-like capabilities of cDC2s in our OvaFla system.…”
Section: Discussionmentioning
confidence: 99%
“…cDC1s present exogenous Ags and secretes IL-12, leading to a cell-based immune response. They present Ags on MHCII to stimulate the activation of CD4 + T helper type 1 cells (Th1), and they are specialized in the cross-presentation of exogenous Ags on MHCI to stimulate the activation CD8 + T cells (cytotoxic killer cells) [ 79 , 80 ].…”
Section: DC Subsets and Their Immunological Rolesmentioning
confidence: 99%